2018 9th IFIP International Conference on New Technologies, Mobility and Security (NTMS) 2018
DOI: 10.1109/ntms.2018.8328741
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Description of Internal Activity on the Ethereum Public Blockchain

Abstract: Abstract-One of the most popular platform based on blockchain technology is Ethereum. Internal activity on this public blockchain is analyzed both from a quantitative and qualitative point of view. In a first part, it is shown that the creation of the Ethereum Alliance consortium has been a game changer in the use of the technology. In a second part, the network robustness against attacks is investigated from a graph point of view, as well as the distribution of internal activity among users. Addresses of grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Ren and Ward [125] found that the percentage of pool-mined blocks was already 91.12% in Bitcoin and 92.2% in Ethereum in July 2018. Mining pool addresses are with the highest degree-based and betweenness centralities in the transaction networks [126].…”
Section: Signature Behaviors Of Cryptocurrency Economy Agents Minersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren and Ward [125] found that the percentage of pool-mined blocks was already 91.12% in Bitcoin and 92.2% in Ethereum in July 2018. Mining pool addresses are with the highest degree-based and betweenness centralities in the transaction networks [126].…”
Section: Signature Behaviors Of Cryptocurrency Economy Agents Minersmentioning
confidence: 99%
“…Overall, it was estimated that 18% of the addresses belonged to exchanges in Bitcoin transactions [72]. Network nodes that belong to popular exchanges are highly ranked in degree [75], [85], PageRank, betweenness, and closeness centralities in the transaction networks [12], [126], [134]. Exchange nodes have particular patterns of network connections, too.…”
Section: Exchanges and Walletsmentioning
confidence: 99%
“…During and after the ICO hype in 2017 the focus of research shifted to topics such as corporate financing and many papers were published dealing with ICOs, their success factors and the value-creation mechanisms behind crypto-tokens (Fisch, 2019;Catalini and Gans, 2018;Florysiak and Schandlbauer, 2019). Several studies conducted descriptive and quantitative (network) analyses on Bitcoin, Ethereum or other cryptocurrencies (Bartoletti and Pompianu, 2017;Anoaica and Levard, 2018;Ferretti and D'Angelo, 2019;Somin et al, 2018;Pinna et al, 2019;Dyson et al, 2020). The work of Bartoletti and Pompianu (2017) itemizes common patterns in the source code of Smart Contracts, while Anoaica and Levard (2018) and Pinna et al (2019) dealt with the identification of high-influence accounts.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies conducted descriptive and quantitative (network) analyses on Bitcoin, Ethereum or other cryptocurrencies (Bartoletti and Pompianu, 2017;Anoaica and Levard, 2018;Ferretti and D'Angelo, 2019;Somin et al, 2018;Pinna et al, 2019;Dyson et al, 2020). The work of Bartoletti and Pompianu (2017) itemizes common patterns in the source code of Smart Contracts, while Anoaica and Levard (2018) and Pinna et al (2019) dealt with the identification of high-influence accounts. pointed out characteristics of Smart Contracts and their creators and showed that most contracts were created by EOAs, however, several contracts were created by other contracts.…”
Section: Related Workmentioning
confidence: 99%
“…The Ethereum is the second most valuable cryptocurrency after the Bitcoin. It is not only a so lution for the digital cryptocurrency, but also supports a vast range of applications based on the smart contracts and the decentralized mechanism over the blockchain networks [34] [9]. Many scenar ios, such as the asset registration, the voting, the management, and the Internet of Things, require a high level of trust, security, and durability.…”
mentioning
confidence: 99%